الاتساق النصي والروابط الإحالية في قصيدة إرادة الحياة لأبي القاسم الشابي دراسة لسانية إحصائية - حسن, أ. م. د. إسراء ياسين (Sulaimani Journal for Humanities, 2023)
The textual consistency and referential links in the poem “The Will of Life” by the poet Abu Al-Qasim Al-Shabi had an integrated weave and a coherent artistic painting that woven art, love and beauty into its interconnected parts, especially since its meanings speak of hope in life and light after darkness, which is what the poet wanted, which is conveying the idea of loving life with its good Evil and its contradictions and unexpected surprises. And that this is evident in the large number of dimensional referrals, which in their referential dimension indicated the strength of the event in this referral through its precedence over others, as well as the hidden pronoun (he), which was mentioned (31) times, as if addressing a person and alerting him to what he wants, and other referrals, pronouns, and cases of links Referral that appeared in the folds of the search as well as the power of replacement between sentences.